Shifting the paradigms in waqf economics: towards renewed focus on socioeconomic development - Abubakar Lamido, Abdullahi; Haneef, Mohamed Aslam (Emerald Publishing Limited, 2021)
This paper critically reviews and analyzes the trends in waqf studies within the Islamic economics literature. It analyzes the recent developments and debates in waqf reform and advances the argument for prioritizing research on waqf economics; the waqf dimension that is concerned with modelling how to utilize it to enhance productivity, consumption, redistribution, investment and saving, and generally contribute sustainably towards poverty reduction, economic empowerment and development.